A short review on passive strategies applied to minimise the building cooling loads in hot locations - Al-Yasiri Qudama; Szabó Márta (2021)
Cooling and air-conditioning systems are responsible for the highest energy consumption in buildings located in hot areas. This high share does not only increase the building energy demand cost but also increases the environmental impact, the topmost awareness of the modern era. The development of traditional systems and reliance on renewable technologies have increased drastically in the last century but still lacks economic concerns. Passive cooling strategies have been introduced as a successful option to mitigate the energy demand and improve energy conservation in buildings. This paper shed light on some passive strategies that could be applied to minimise building cooling loads to encourage the movement towards healthier and more energy-efficient buildings. For this purpose, seven popular passive technologies have been discussed shortly: multi-panned windows, shading devices, insulations, green roofing, phase change materials, reflective coatings, and natural ventilation using the windcatcher technique. The analysis of each strategy has shown that the building energy could be improved remarkably. Furthermore, adopting more passive strategies can significantly enhance the building thermal comfort even under severe weather conditions.
Keywords: Műszaki és technológiai tudományok; Építőmérnöki tudományok